Pristopi k izdelavi leksikalnih podatkovnih zbirk - Fišer, Darja (Jezik in slovstvo, 2005)
The paper presents WorldNet and EuroWorldNet, lexical databases in which concepts are linked with lexical and semantic relations. In the past decade, similar lexical databases for other languages have been based on them, for which two approaches have mostly been used: the creation of independant wordnets and their subsequent integration into multilingual lexical databases, and the expansion of existing lexical databases into the target language by translating the entries and adopting relations between them. Due to the great automation potential of the network creation process and a uniform structure of the resulting databases, the latter approach has become very popular. This is why the given model was tested in this paper for its ability to create a Slovene wordnet, and the results were compared to its language-motivated counterpart acquired from the Fida corpus as well as other mono- and multilingual language resources for Slovene.
Keywords: Corpus linguistics; FIDA; korpusno jezikoslovje; leksikografija; lexicography; podatkovne zbirke; Slovene; slovenščina